2009
DOI: 10.1007/s11661-009-9940-z
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Mechanical Response of Equal-Channel Angular Extrusion-Processed Al-40Zn-2Cu Alloy

Abstract: Microstructural evolution, tensile properties, and impact toughness of an aluminum-zinccopper (Al-40Zn-2Cu) alloy subjected to repetitive equal-channel angular extrusion (ECAE) up to four passes following either route A or route B C were investigated. The experimental results reveal that the ECAE eliminated as-cast dendritic microstructure along with casting defects such as microporosities almost completely. The ECAE-processed samples consisted of mostly elongated microconstituents via route A and equiaxed mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…[2] Ultrafine-grained (UFG) materials produced by severe plastic deformation (SPD) with grain sizes in the range of 100 to 1000 nm have received considerable attention due to their higher strength combined with an adequate ductility compared to their coarse-grained (CG) counterparts. [3][4][5][6][7][8][9][10][11][12][13] Among the available SPD methods, equalchannel angular extrusion (ECAE) is considered to be the most capable one to control the resulting microstructural features of the UFG materials like grain size, grain morphology, and grain boundary character. [14,15] UFG materials have been identified as promising candidates for micro-forming processes due to their submicron-sized structures.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Ultrafine-grained (UFG) materials produced by severe plastic deformation (SPD) with grain sizes in the range of 100 to 1000 nm have received considerable attention due to their higher strength combined with an adequate ductility compared to their coarse-grained (CG) counterparts. [3][4][5][6][7][8][9][10][11][12][13] Among the available SPD methods, equalchannel angular extrusion (ECAE) is considered to be the most capable one to control the resulting microstructural features of the UFG materials like grain size, grain morphology, and grain boundary character. [14,15] UFG materials have been identified as promising candidates for micro-forming processes due to their submicron-sized structures.…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour occurring after further deformation can be attributed to the deformation induced homogenisation of the phases. This homogenisation effect in Zn-Al alloys during warm equal channel angular extrusion processing was the main topic of the study performed by Purcek et al 26 In that study, the reason of worksoftening was discussed, and they found that individual phase compositions in two phase as cast alloys approached to each other and the volume fraction of the hard phase dropped with the number of equal channel angular extrusion passes in relatively high processing temperature (T H 50?41). They concluded that further deformation had no considerable effect on strengthening of the as cast alloy.…”
Section: Hardness Tensile and Impact Propertiesmentioning
confidence: 98%
“…The mechanical properties of Al-Zn alloys are strongly influenced by dendritic structure as indicated in previous studies. 26,31,32 Shrinkage microporosities formed as a result of dendritic solidification limit the strength and ductility of the alloy due to the increased cracking tendency. 32 McKenzie et al 33 studied the porosity reduction during ECAP and found that the number of pores in the as cast structure significantly decreased with ECAP.…”
Section: Hardness Tensile and Impact Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For commercial purity Al deformed after multi-pass ECAP, it has been found that compared to route Bc, the texture strength developed in route C is higher up to four passes [20]. So far, ECAP has been applied to some Al-Zn alloys with eutectic [39], eutectoid [40] and monotectoid compositions [41], whereas there appears to be a lack of investigations on the texture evolution of binary Al-Zn alloys containing less than 10 wt.% Zn during large number of ECAP passes. In addition to ECAP route and number of passes, annealing is expected to be another factor that can influence the formation of microstructures and textures.…”
Section: Introductionmentioning
confidence: 99%